Hubungan Antara Psikologi Islam Dan Penanganan Tekanan Emosional: Tinjauan Terhadap Strategi Dan Pendekatan Berbasis Islam Dalam Mengatasi Stres Pada Pola Asuh Nenek - Risydah Fadilah; Tiara Putri Mahisani; Wahyuni Dazura (Universitas Katolik Widya Karya Malang, 2023)
This article aims to find out and describe the relationship between Islamic psychology and the handling of emotional stress and the involvement of grandmother's parenting. The methods used in this study were literature study, observation, and interviews to find out about the relationship between Islamic psychology and emotional stress management. Islamic psychology is a field of study that combines Islamic principles and teachings with modern psychological principles to understand human behavior and offers a holistic approach in understanding and treating psychological problems. Emotional distress, or emotional stress, is a state of emotional imbalance that occurs when individuals encounter emotionally challenging situations or events. Parenting that is not good will make the child become a closed person and lack confidence. This article was written with the aim of conveying information to the reader, so that it can be used as a reference to increase the reader's knowledge, and can have an academic impact on the writer. This article contains the relationship between Islamic psychology and dealing with emotional stress and the involvement of grandmothers in parenting.